The challenges for Ukrainian theatre art in the years 2020-2022 - M. I. Korobko (Ukrainian Cultural Studies, 2022)
The purpose pf the article is to monitor the challenges faced by Ukrainian theater during the global coronavirus crisis and the war in Ukraine in 2020-2022. During its long history, the Ukrainian theater has experienced various difficulties: bans (the Ems Act and the Valuev Circular in the 19th century), strict censorship (in the late 19th century and almost all of the 20th century), and two World Wars. General socio-cultural factors, political crises and, finally, war were also added to the background of the great theatrical crisis, which was present even before 2020. Responding to the challenges of the times, the theater searches for and develops new models of broadcasting and communication with its audience. But Ukrainian theaters, unlike their Western counterparts, were able to open in mid-2020 and more or less work in 2021. The XXI century was marked by difficult pandemics in 2020 and 2021 and the war in Ukraine (which lasted from 2014 in Donetsk and Luhansk regions, the occupation of Crimea and the spread of war throughout our country in 2022). In addition to objective geopolitical problems, there are problems of new political reforms, underfunding, and lack of professional staff (because the theater is not only actors and directors, but also educators, playwrights, and cultural audience, and various workers, whose audience not to see). All these factors have called into question the existence of even large professional theaters, not to mention smaller and unprofitable theaters. The theater is now in a particularly difficult situation, almost on the verge of extinction. Theatrical workers are trying to find new ways to express themselves and attract spectators, sponsors and funds in order to survive. They are looking for new genres, new drama, new themes for their performances. At the moment, almost all theater groups are trying to find non-standard forms of work: online screenings, immersion performances, open-air performances and more. The problems became bigger when the full-scale war started in February 24. However, Ukrainian theaters reopened their doors for spectators in April, after the month of total silence and non-action. And this fact gives us the hope for living.